A 180° Tunable Analog Phase Shifter Based on a Single All‐Pass Unit Cell. Issue 12 (23rd September 2013) - Khoder, K.; Pérennec, A.; Le, M.
ABSTRACT This article describes an analog phase shifter able to provide a continuously tunable phase shift up to 180° by using a single all‐pass unit cell. The proposed topology is compact and easy to implement, and brings an interesting compromise between phase variation, insertion and return losses. Indeed, for a 7.5:1 tuning ratio of varactor capacitance, a phase shift variation of more than 186° is obtained from 6 to 7 GHz with a maximum insertion loss of 1.8 dB. The 105°/dB resulting Figure‐of‐Merit is thus among the best in distributed approaches with varactors. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2915–2918, 2013